First complete mitogenome assembly of Castanea sativa: structure, comparative genomics, and phylogeny - Sara Villa; Alexis Marchesini; Sara Torre; Luca Bianco; Paolo Fontana; Concetta De Quattro; Mirko Moser; Stefano Piazza; Sara Alessandri; Vera Pavese; Paola Pollegioni; Cristiano Vernesi; et al. (Tree Genetics & Genomes, 2025)

Paint it green: A neuroscientific approach to hotel sustainability and ecological tourism - Giulia Fronda; Federico Cassioli; Roberta Sebastiani; Annalisa Beatrice Galeone; Michela Balconi (Environment, Development and Sustainability, 2021)

Correction to: Effect of longevity genetic variants on the molecular aging rate - Anastasia Gurinovich; Zeyuan Song; William Zhang; Anthony Federico; Stefano Monti; Stacy L. Andersen; Lori L. Jennings; David J. Glass; Nir Barzilai; Sofiya Millman; Thomas T. Perls; Paola Sebastiani (GeroScience, 2021)

Effect of longevity genetic variants on the molecular aging rate - Anastasia Gurinovich; Zeyuan Song; William Zhang; Anthony Federico; Stefano Monti; Stacy L. Andersen; Lori L. Jennings; David J. Glass; Nir Barzilai; Sofiya Millman; Thomas T. Perls; Paola Sebastiani (GeroScience, 2021)

Multispecies genetic structure and hybridization in the Betula genus across Eurasia - Yoshiaki Tsuda; Vladimir Semerikov; Federico Sebastiani; Giovanni Giuseppe Vendramin; Martin Lascoux (Molecular Ecology, 2017)
Boreal and cool temperate forests are the major land cover of northern Eurasia, and information about continental‐scale genetic structure and past demographic history of forest species is important from an evolutionary perspective and has conservation implications. However, although many population genetic studies of forest tree species have been conducted in Europe or Eastern Asia, continental‐scale genetic structure and past demographic history remain poorly known. Here, we focus on the birch genus Betula , which is commonly distributed in boreal and cool temperate forests, and examine 129 populations of two tetraploid and four diploid species collected from Iceland to Japan. All individuals were genotyped at seven to 18 nuclear simple sequence repeats ( nSSR s). Pairwise among the six species ranged from 0.285 to 0.903, and genetic differentiation among them was clear. structure analysis suggested that Betula pubescens is an allotetraploid and one of the parental species was Betula pendula . In both species pairs of B. pendula and B. plathyphylla , and B. pubescens and B. ermanii , genetic diversity was highest in central Siberia. A hybrid zone was detected around Lake Baikal for eastern and western species pairs regardless of ploidy level. Approximate Bayesian computation suggested that the divergence of B. pendula and B. platyphylla occurred around the beginning of the last ice age (36 300 years BP , 95% CI : 15 330–92 700) and hybridization between them was inferred to have occurred after the last glacial maximum (1614 years BP , 95% CI : 561–4710), with B. pendula providing a higher contribution to hybrids.

A sample view of the pedunculate oak (Quercus robur) genome from the sequencing of hypomethylated and random genomic libraries - Isabelle Lesur; Jérome Durand; Federico Sebastiani; Niclas Gyllenstrand; Catherine Bodénès; Martin Lascoux; Antoine Kremer; Giovanni G. Vendramin; Christophe Plomion (Tree Genetics & Genomes, 2011)

Variation in the chloroplast DNA of Swiss stone pine ( Pinus cembra L.) reflects contrasting post‐glacial history of populations from the Carpathians and the Alps - Maria Höhn; Felix Gugerli; Peter Abran; György Bisztray; Anna Buonamici; Klara Cseke; Levente Hufnagel; Celestino Quintela‐Sabarís; Federico Sebastiani; Giovanni Giuseppe Vendramin (Journal of Biogeography, 2009)
Aim To characterize the genetic structure and diversity of Pinus cembra L. populations native to two disjunct geographical areas, the Alps and the Carpathians, and to evaluate the rate of genetic differentiation among populations. Location The Swiss Alps and the Carpathians. Methods We screened 28 populations at three paternally inherited chloroplast simple sequence repeats (cpSSRs) for length variation in their mononucleotide repeats. Statistical analysis assessed haplotypic variation and fixation indices. Hierarchical analysis of molecular variance (AMOVA), Mantel test, spatial analysis of molecular variance (SAMOVA) and barrier analyses were applied to evaluate the geographical partitioning of genetic diversity across the species’ range. Results Haplotypic diversity was generally high throughout the natural range of P. cembra , with the mean value substantially higher in the Carpathians ( H = 0.53) than in the Alps ( H = 0.35). The isolated Carpathian populations showed the highest haplotype diversity among the populations originating from the High Tatras (Velka Studena Dolina) and South Carpathians (Retezat Mountains). AMOVA revealed that only 3% of the total genetic variation derived from genetic differentiation between the two mountain ranges. Differentiation among Carpathian populations was higher ( F ST = 0.19) than among Alpine populations ( F ST = 0.04). Low, but significant, correlation was found between the geographical and genetic distances among pairs of populations ( r = 0.286, P 0.001). SAMOVA results revealed no evident geographical structure of populations. barrier analysis showed the strongest differentiation in the eastern part of the species’ range, i.e. in the Carpathians. Main conclusions The populations of P. cembra within the two parts of the species’ range still share many cpDNA haplotypes, suggesting a common gene pool conserved from a previously large, continuous distribution range. Carpathian populations have maintained high haplotypic variation, even higher than Alpine populations, despite their small population sizes and spatial isolation. Based on our results, we emphasize the importance of the Carpathian populations of Swiss stone pine for conservation. These populations comprise private haplotypes and they may represent a particular legacy of the species’ evolutionary history.

Isolation and characterization of polymorphic nuclear microsatellite loci in Taxus baccata L. - Marta Dubreuil; Federico Sebastiani; Maria Mayol; Santiago C. González-Martínez; Miquel Riba; Giovanni G. Vendramin (Conservation Genetics, 2008)

Range‐wide phylogeography and gene zones in Pinus pinaster Ait. revealed by chloroplast microsatellite markers - GABRIELE BUCCI; SANTIAGO C. GONZÁLEZ‐MARTÍNEZ; GRÉGOIRE LE PROVOST; CHRISTOPHE PLOMION; MARIA MARGARIDA RIBEIRO; FEDERICO SEBASTIANI; RICARDO ALÍA; GIOVANNI GIUSEPPE VENDRAMIN (Molecular Ecology, 2007)
Some 1339 trees from 48 Pinus pinaster stands were characterized by five chloroplast microsatellites, detecting a total of 103 distinct haplotypes. Frequencies for the 16 most abundant haplotypes ( p k > 0.01) were spatially interpolated over a lattice made by 430 grid points. Fitting of spatially interpolated values on raw haplotype frequencies at the same geographical location was tested by regression analysis. A range‐wide ‘diversity map’ based on interpolated haplotype frequencies allowed the identification of one ‘hotspot’ of diversity in central and southeastern Spain, and two areas of low haplotypic diversity located in the western Iberian peninsula and Morocco. Principal component analysis (PCA) carried out on haplotypes frequency surfaces allowed the construction of a colour‐based ‘synthetic’ map of the first three PC components, enabling the detection of the main range‐scale genetic trends and the identification of three main ‘gene pools’ for the species: (i) a ‘southeastern’ gene pool, including southeastern France, Italy, Corsica, Sardinia, Pantelleria and northern Africa; (ii) an ‘Atlantic’ gene pool, including all the western areas of the Iberian peninsula; and (iii) a ‘central’ gene pool, located in southeastern Spain. Multivariate and amova analyses carried out on interpolated grid point frequency values revealed the existence of eight major clusters (‘gene zones’), whose genetic relationships were related with the history of the species. In addition, demographic models showed more ancient expansions in the eastern and southern ranges of maritime pine probably associated to early postglacial recolonization. The delineation of the gene zones provides a baseline for designing conservation areas in this key Mediterranean pine.

RAPD-derived, PCR-based mitochondrial markers for Larix species and their usefulness in phylogeny - Vladimir L. Semerikov; Giovanni G. Vendramin; Federico Sebastiani; Martin Lascoux (Conservation Genetics, 2006)